Are we teaching UML according to what IT companies need? A survey on the São Carlos-SP region - Choma Neto, João; Bento, Luiz Henrique Ten Caten; OliveiraJr, Edson; Souza, Simone Do Rocio Senger (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2021: Anais do Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2021.14469, 2021)
The Unified Modeling Language (UML) arisen intending to unify the many modeling languages and become the universal language for software modeling. Since its creation, more than 25 years have passed. With the growing success of agile methodologies for software development, supported by less modeling and documentation manifest, the use of UML-driven software processes has decreased, thus a specific subset of diagrams has been adopted, such as use case, class, and sequence. On the other hand, in academia, UML is still being taught in Computing courses, most of the time without knowing whether what is taught is what the industry needs for practical use. This paper presents an overview of the UML adoption in IT companies of the region. We analyzed quantitative and qualitative data to support academia at focusing on the most used UML diagrams by practitioners. We constructed a survey composed of 21 questions, distributed to 10 region companies, and we received 24 answers. The results of our study show high usage of UML, including companies adopting agile methods. Certain diagrams are more intensively used, for instance, use case diagrams. The results provide directions to improve UML teaching, focusing on diagrams that best adhere to the development processes employed, in particular, agile processes.